Johnson's map of the world on Mercator's projection. - Johnson, A. J. (Alvin Jewett), 1827-1884 (Johnson and Ward, 1862)
Map shows early nineteenth century cities and geography of Africa, Asia, North America, south America, Europe, and Oceania. Exploration routes of Captain James Cook and Captain Charles Wilkes are noted. Relief shown by hachures. Scale [ca.1:67,000,000].